(untitled) (Al-Academy, 2023)
This research talked about the importance of adjacent structures for informing the stage show for children. The researcher began from the importance of adjacent structures for informing the show to introduce the various and different proofs, on the level of creativity and artistic shape of the accomplishment over it’s shifts that contribute to formation the show and it’s intellectual, artistic, technical and cognitive Marks that contribute in dynamism the interactive show and contact the idea that connect with the design and directional vision for the beauty and cognitive. Lead to the eager operation in attention, sensitive and attractive the child. The research consist of four chapters: The first chapter include methodological framework of the research. The problem of the research is based on the question: What is the shapes of the adjacent structures in informing the stage show for the children? The importance of the research concerning in the adjacent structure of the art stage and it’s work in informing the state show for children and it’s aim to know the mechanism of the adjacent structures or the art age stage according to the styles and directions of its designers. The research benefit the workers’ interestings and specialist in the child art stage. The research conclude to set the expressions. The second chapter concerning about the adjacent structures of informing the presentation of a stage show for children. The research concluded over the results of theoretical fram. As for the third chapter concerning about the research measures, the sample was chosen according to the analyzing descriptive approach. While the fourth chapter include the results that the researcher founded in informing the adjacent structures of the stage show to introduce different evidences on the level of the creative and artistic shape of the project. The research concluded with several suggestions and recommendations and the list of references and attaches and additions of translation the abstract into English.